Optimization for drilling process of metal-composite aeronautical structures - Devitte Cristiano (De Gruyter, 2021)
Metal-composite laminates and joints are applied in aircraft manufacturing and maintenance (repairing) using aluminum alloys (AA) and glass fiber-reinforced polymer (GFRP). In these applications, drilling has a prominent place due to its vast application in aeronautical structures’ mechanical joints. Thus, this study presents the influence of uncoated carbide drills (85C, 86C, H10N), cutting speeds (v c = 20, 40, and 60 m min−1), and feed rates (f = 0.05, 0.15, and 0.25 mm rev−1) on delamination factor, thrust force (FtF_{\text{t}}), and burr formation in dry drilling metal-composite laminates and joints (AA2024/GFRP/AA2024). Experiments were performed, analyzed, and optimized using the Box–Behnken statistical design. Microscopic digital images for delamination evaluation, piezoelectric dynamometer for thrust force acquisition, and burr analysis were considered. The major finding was that the thrust force during drilling depends significantly on the feed rate. Another significant factor was the influence of the drill type (combined or not with feed rate). In fact, it was verified that the feed rate and the drill type were the most significant parameters on the delamination factor, while the feed rate was the most relevant on thrust force. The cutting speed did not affect significantly thrust force and delamination factor at exit(FdaS)\hspace{.25em}(F_{{\text{da}}_{\text{S}}}). However, the combination f × v c was significant in delamination factor at entrance (FdaE)\text{ }(F_{{\text{da}}_{\text{E}}}). Based on the optimized input parameters, they presented lower values for delamination factors (FdaE=1.18F_{{\text{da}}_{\text{E}}}=1.18 and FdaS=1.33F_{{\text{da}}_{\text{S}}}=\hspace{.25em}1.33) and thrust force (Ft=67.3NF_{\text{t}}=67.3\hspace{.5em}\text{N}). These values were obtained by drilling the metal-composite laminates with 85C-tool, 0.05 mm rev−1 feed rate, and 20 m min−1 cutting speed. However, the burrs at the hole output of AA2024 were considered unsatisfactory for this specific condition, which implies additional investigation.